2013
DOI: 10.1016/j.respol.2012.10.008
|View full text |Cite
|
Sign up to set email alerts
|

The periphery on stage: The intra-organizational dynamics in online communities of creation

Abstract: This is the accepted version of the paper.This version of the publication may differ from the final published version. Permanent City Research OnlineThe periphery on stage:The intra-organizational dynamics in online communities of creation Francesco Rullani LUISS Guido CarliStefan Haefliger ETH Zurich July 2012 AbstractThis paper theorizes the intra-organizational dynamics of online communities of creation such as Free and Open Source software projects. It describes the role of the participants at the periphe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
65
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(71 citation statements)
references
References 104 publications
3
65
0
2
Order By: Relevance
“…Open source software development is organized in communities that comprise both individual users and firms, represented by employees (Levine andPrietula, 2013, Rullani andHaefliger, 2013;Lakhani & von Hippel, 2003;Spaeth, von Krogh, & Fang He, 2014). New forms of collaboration (e.g., Börjeson, 2015;Howison and Crowston, 2014;Iturrioz, Aragon, & Narvaiza, 2015) can trigger both updates in social practice and conflict in terms of agenda setting, for the community or for the individual participants in an organization.…”
Section: Discussionmentioning
confidence: 99%
“…Open source software development is organized in communities that comprise both individual users and firms, represented by employees (Levine andPrietula, 2013, Rullani andHaefliger, 2013;Lakhani & von Hippel, 2003;Spaeth, von Krogh, & Fang He, 2014). New forms of collaboration (e.g., Börjeson, 2015;Howison and Crowston, 2014;Iturrioz, Aragon, & Narvaiza, 2015) can trigger both updates in social practice and conflict in terms of agenda setting, for the community or for the individual participants in an organization.…”
Section: Discussionmentioning
confidence: 99%
“…In their widely-cited article, Mockus et al (2002) reported the differences of contribution types and scale between core developers and the other contributors: a group larger than the core by about an order of magnitude contributed to defect fixing, and a group larger by another order of magnitude contributed to defect reporting. Rullani and Haefliger (2013) described the roles of core developers and those in the peripheries, and how the propagation of such standards is communicated through non-material artifacts such as code and virtual discussions as a social practice.…”
Section: Differences Between Core and Peripherymentioning
confidence: 99%
“…For example, Crowston and Howison [2] see community-based FLOSS teams as having an onion-like core-periphery structure, in which the core category includes core developers and the periphery includes co-developers and active users. Rullani and Haefliger [10] described periphery as a "cloud" of members that orbits around the core members of open source software development teams.…”
Section: Introductionmentioning
confidence: 99%
“…It is evident that, by making direct contributions to the software developed, core members are vital to project development. On the other hand, even though they contribute only sporadically, peripheral members provide bug reports, suggestions and critical expertise that are fundamental for innovation [10]. In addition, the periphery is the source of new core members [12,13], so maintaining a strong periphery is important to the longterm success of a project.…”
Section: Introductionmentioning
confidence: 99%